Odpowiedzi

Najlepsza Odpowiedź!
2009-12-13T15:42:44+01:00
Cześć. :)))

Oto rozwiązania ^^

a) (x-1)²-(x+4)²= -2x+1

x²-2x+1-x²-8x-16= -2x+1

-8x-15=1

-8x=16

x=-2


b) (x+5)²-(x-3)²=x+1

x²+10x+25-x²+6x-9=x+1

15x=1+9-25

15x=-15

x=-1


c) (x -5)²-(x-3)²=4(x-2)

x²-10x+25-x²+6x-9=4x-8

-8x=-24

x=3


Liczę na naj :)))
1 5 1
2009-12-13T15:54:02+01:00
A) x²-2x+1-(x²+8x+16)=-2x+1
x²-2x+1-x²-8x-16=-2x+1
-2x-8x+2x=1-1+16
-8x=16/(-8)
x=-2
b) (x+5)²-(x-3)²=x+1
x²+10x+25-(x²-6x+9)=x+1
x²+10x+25-x²+6x-9=x+1
10x+6x-x=1-25+9
15x=-15/15
x=-1
c) (x -5)²-(x-3)²=4(x-2)
x²-10x+25-(x²-6x+9)=4x-8
x²-10x+25-x²+6x-9=4x-8
-10x+6x-4x=-8-25
-8x=-33/(-8)
x=4⅛
1 1 1
2009-12-13T15:56:51+01:00
A) (x-1)²-(x+4)²= -2x+1
x²-2x+1-(x²+8x+16)=-2x+1
x²-2x+1-x²-8x-16=-2x+1.................x² i -x² skrócą się
-2x-8x+2x=1+16-1
-8x=16/÷(-8)
x=-2

b) (x+5)²-(x-3)²=x+1
x²+10x+25-(x²-6x+9)=x+1
x²+10x+25-x²+6x-9=x+1
10x=1+9
10x=10/÷ 10
x=1

c) (x -5)²-(x-3)²=4(x-2)
x²-10x+25-(x²-6x+9)=4x-8
x²-10x+25-x²+6x-9=4x-8
-10x+6x-4x=-8+9-25
-8x=-24/÷(-8)
x=3
1 1 1